2016
DOI: 10.1111/jvs.12485
|View full text |Cite
|
Sign up to set email alerts
|

Effects of coarse woody debris on plant and lichen species composition in boreal forests

Abstract: Question Although the importance of coarse woody debris (CWD) for understorey species diversity has been recognized, the relative effects of coarse woody debris decay class and substrate species on understorey species composition have received little attention. We examined how the species composition of understorey vegetation change with CWD decay class and substrate species. Location Boreal mixed‐wood forests, Ontario, Canada. Methods To cover a wide range of CWD decay classes and substrate species, we sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 68 publications
(190 reference statements)
4
26
0
Order By: Relevance
“…We found that substrate diversity was positively associated with stand age, which indirectly increased the overall understorey species richness but not cover. This result is consistent with increases in microsite heterogeneity in the form of tip-up mounds and coarse woody debris with increasing stand age (Bartels & Chen, 2010;Brassard & Chen, 2006;Kumar et al, 2017b;Mills & Macdonald, 2004) Messier, & Canham, 2006;Macdonald & Fenniak, 2007), and are generally more productive than conifer or broadleaf stands (Zhang, Chen, & Reich, 2012;Zhang et al, 2017). Enhanced productivity is expected to result in accelerated stand development and self-thinning; this is expected to enhanced substrate diversity in the form of coarse woody debris and exposed mineral soil in productive or mixed-wood stands (e.g.…”
Section: Discussionsupporting
confidence: 66%
See 3 more Smart Citations
“…We found that substrate diversity was positively associated with stand age, which indirectly increased the overall understorey species richness but not cover. This result is consistent with increases in microsite heterogeneity in the form of tip-up mounds and coarse woody debris with increasing stand age (Bartels & Chen, 2010;Brassard & Chen, 2006;Kumar et al, 2017b;Mills & Macdonald, 2004) Messier, & Canham, 2006;Macdonald & Fenniak, 2007), and are generally more productive than conifer or broadleaf stands (Zhang, Chen, & Reich, 2012;Zhang et al, 2017). Enhanced productivity is expected to result in accelerated stand development and self-thinning; this is expected to enhanced substrate diversity in the form of coarse woody debris and exposed mineral soil in productive or mixed-wood stands (e.g.…”
Section: Discussionsupporting
confidence: 66%
“…Coarse woody debris is the most abundant source of substrate heterogeneity in this system; in related work, we found that early decayclass woody debris showed much lower total vegetation cover than did the forest floor (Kumar et al, 2017b).…”
Section: Discussionmentioning
confidence: 50%
See 2 more Smart Citations
“…Indeed, shade‐preferring species and species with crustose growth form have been characterized as fire‐vulnerable (Johansson et al., ), and at the tree scale, microlichens have a slightly slower initial post‐fire recovery compared to macrolichens (Hämäläinen, Kouki, & Lõhmus, ). The positive impact of logs in old burns can be linked with the supply of specific microhabitats (Kumar, Chen, Thomas, & Shahi, ). Macrolichens benefit most strongly, in particular this is seen for Cladonia species that are typical inhabitants of downed, decayed wood (Botting & DeLong, ; Söderström, ).…”
Section: Discussionmentioning
confidence: 99%